Stairway to Heaven, Cosmos, and Life: A Journey from Mythology to Reality - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
This review examines the intersection of cultural mythology, cosmological science, and existential philosophy through the lens of Led Zeppelin's iconic song